2020
DOI: 10.1177/0363546520964445
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Cell Sheets for the Effective Delivery of Adipose-Derived Stem Cells for Tendon-to-Bone Healing

Abstract: Background: Efforts are being made to treat rotator cuff tears (RCTs) that exhibit poor healing and high retear rates. Tendon-to-bone healing using mesenchymal stem cells is being explored, but research is needed to establish effective delivery options. Purpose: To evaluate the effects of an adipose-derived stem cell (ADSC) sheet on mesenchymal stem cell delivery for tendon-to-bone healing of a chronic RCT in rats and to demonstrate that ADSC sheets enhance tendon-to-bone healing. Study Design: Controlled labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 47 publications
0
35
0
1
Order By: Relevance
“…TDSCs have reparative properties in tendon injury, exhibiting spontaneous tenogenic differentiation potentials in vitro. 22 H19 has previously been reported to promote tenogenic differentiation of human TDSCs. 18 To confirm this, rat TDSCs were isolated and cultured, and stable H19-overexpression (H19) and H19-shRNA (shH19) TDSCs were generated using a lentiviral system and confirmed by RT-qPCR.…”
Section: Resultsmentioning
confidence: 96%
“…TDSCs have reparative properties in tendon injury, exhibiting spontaneous tenogenic differentiation potentials in vitro. 22 H19 has previously been reported to promote tenogenic differentiation of human TDSCs. 18 To confirm this, rat TDSCs were isolated and cultured, and stable H19-overexpression (H19) and H19-shRNA (shH19) TDSCs were generated using a lentiviral system and confirmed by RT-qPCR.…”
Section: Resultsmentioning
confidence: 96%
“…studied a scaffold free tissue-engineered tendon graft designed for rotator cuff repair, compared with the suture group, the graft group had more orderly collagenous fiber arrangement. Shin, M. J [ 129 ] investigated the results of adipose stem cell sheets and found that there was more fibrochondrogenic formation in the cell sheet group compared with the simple suture group. Varvitsiotis, D [ 130 ] studied allograft fascia lata and compared with simple suture, both groups showed fibroblast growth and collagen fibers at the tendon-bone interface without significant differences.…”
Section: Resultsmentioning
confidence: 99%
“…After the deltoid was split, the supraspinatus tendon was separated and transected from its footprint on the greater tuberosity. Thereafter, the distal supraspinatus tendon was wrapped with a small elastic drainage tube to prevent spontaneous reattachment of the supraspinatus tendon to the greater tuberosity (see Appendix Figure A1, available in the online version of this article), 22,38 followed by a routine layer-by-layer closure.…”
Section: Methodsmentioning
confidence: 99%
“…Keywords: rotator cuff repair; osteoporosis; anabolic; abaloparatide; antiresorptive; denosumab; tendon-to-bone Rotator cuff tears (RCTs) are among the most common disorders that result in shoulder pain and functional disabilities. 10,12,38 Despite rapid improvements in repair techniques and instrumentation, high rates of failure are reported, as high as 94% in patients with massive tears. 26,37,48 Multiple reasons account for healing failure after a rotator cuff repair, such as fatty infiltration, muscle atrophy, and degeneration of the tendon.…”
mentioning
confidence: 99%